2020
DOI: 10.1002/hed.26354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and validation of Physiological and Operative Severity Score for the enumeration of mortality and morbidity and Portsmouth‐POSSUM scores in predicting morbidity and mortality in patients undergoing head and neck cancer surgeries

Abstract: Background Identification of risk factors for perioperative complications helps in the prognostication. We wanted to determine whether Physiological and Operative Severity Score for the enumeration of mortality and morbidity (POSSUM) and Portsmouth‐POSSUM (P‐POSSUM) can be used in patients undergoing head and neck oncosurgery. Methods We conducted a retrospective analysis of 1265 patients after they had major head and neck oncosurgeries. Demographic, surgical and outcome data was collected. We separately analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Our study showed that a higher POSSUM score matched with higher mortality and was also statically eloquent. Karan et al stated that the POSSUM score was good at predicting morbidity [21]. However, they were not able to check the usefulness of the scores for mortality because no death occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that a higher POSSUM score matched with higher mortality and was also statically eloquent. Karan et al stated that the POSSUM score was good at predicting morbidity [21]. However, they were not able to check the usefulness of the scores for mortality because no death occurred.…”
Section: Discussionmentioning
confidence: 99%